1995
DOI: 10.3382/ps.0740523
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Proteolytic Enzymes in Chicken Muscles. Differences Among Strains with Different Growth Rates and Protein Efficiencies

Abstract: The theory that net muscle growth is, at least partly, regulated by catabolic factors has been tested in order to set up an animal model to study meat aging and post-mortem tenderization. Male and female chickens of a layer strain (White Leghorn), a commercial broiler strain (Ross), and two experimental broiler lines (designated GL and FC) were used to estimate differences in proteolytic enzyme activities in the breast muscles. The GL and the FC lines were selected for high body weight gain and high feed effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 44 publications
2
30
0
2
Order By: Relevance
“…Schreurs et al (1995) investigated the contribution of the Ca 2ĂŸ -dependent proteolysis for the normal development of different chicken strains and showed that there was less calpain activity, but more calpastatin, in muscles from chicken genetically selected for growth. Thus, a good strategy to promote growth of farm animals seems to be the reduction of the Ca 2ĂŸ -dependent protein degradation (Goll et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Schreurs et al (1995) investigated the contribution of the Ca 2ĂŸ -dependent proteolysis for the normal development of different chicken strains and showed that there was less calpain activity, but more calpastatin, in muscles from chicken genetically selected for growth. Thus, a good strategy to promote growth of farm animals seems to be the reduction of the Ca 2ĂŸ -dependent protein degradation (Goll et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…50 The aspartate proteinase, CTSD (EC 3.4.23.5), was assayed spectrophotometrically (Uvikon 930, Kontron Instruments) at 280 nm according to the procedure described by Takahashi and Tang, 51 with minor modifications. 32 The CTSD/CTSB activity ratio was also calculated for each biological type and aging time.…”
Section: Cathepsin Activitiesmentioning
confidence: 99%
“…Interestingly, the phenotypic differences between the two chicken breeds arise as early as the first few days of embryonic development (Clum et al, 1995;Burggren et al, 2004;Boerjan, 2004), potentially setting the stage for the breed-specific differences observed in latestage embryonic (Sato et al, 2006;Everaert et al, 2008), juvenile (Martinez-Lemus et al, 1999;Latimer and Brisbin, 1987;Odom et al, 2004) and adult (Martinez-Lemus et al, 1998;Koenen et al, 2002;Schreurs et al, 1995;McRae et al, 2006) phenotypes. Broiler embryos have faster overall development rates than layer embryos, which is first evident at 48h of development (Boerjan, 2004;Everaert et al, 2008).…”
Section: Introductionmentioning
confidence: 99%